Drying Characteristics of Malaysian Padi - Wan Daud, Wan Ramli; Haque Sarker, Muhammad Niazul; Meor Talib, Meor Zainal (Universiti Putra Malaysia Press, 2000)
In this paper, the drying behaviour of Malaysian padi was studied using the thin layer method. Characteristic drying curves of padi were determined using an environmental chamber. The experiments were conducted over a temperature range of between 30°C to 70°C, air relative humidity from 30% to 80% and air velocity from 0.12 to 1 m/s. No constant rate periods was observed. Mass loss, temperature, relative humidity and air velocity were monitored on a personal computer. From the drying curves, two falling rate periods were observed, namely an initial rapid drying period and a subsequent gradual drying period. The normalised drying rate versus normalised moisture content was regressed by least square method to fit a new polynomial model for the first falling rate period and a linear model for the second falling rate period. Both the polynomial and linear models estimate the falling rate periods quite well